Analisis Angka Harapan Hidup, Penyerapan Tenaga Kerja, dan Tingkat Kemiskinan di Kabupaten Serang - Devikartini, Sekar Ayu; Asmara, Kiky (Universitas Hamzanwadi, 2024)
The Human Development Index is in the 3rd lowest position among other regions in Banten Province. This is due to labor absorption, low life expectancy, labor absorption which is always fluctuating which can cause poverty levels to increase. It is necessary to strive to increase human development in order to improve the quality of society in Serang Regency. This research is aimed at analyzing the human development index in Serang Regency. Using the variables life expectancy, labor absorption and poverty levels with secondary data in the form of time series data for 13 years, namely from 2010 to 2022 obtained from BPS Banten Province and BPS Serang Regency. This research uses an analytical tool in the form of E-views 12 software. The research results obtained are that life expectancy has a positive and significant effect on HDI, labor absorption has a negative effect on HDI, and poverty levels also have a negative effect on HDI in Serang Regency.